PENGARUH PEMBANGUNAN KOTA TERHADAP BEBAN KERJA PEREMPUAN MISKIN DI KOTA JAKARTA - Veronica Kumurur (EKOTON, 2014)
Urban development not only generate economic growth and environmental degradation, such as air pollution, pollution of river water and ground water. Both of these constitute a social gap for the city of Jakarta. Where these gaps become a heavy burden for the poor city of Jakarta. Heaviness of the same was not felt by the poor men and poor women of Jakarta. Women who have experienced poverty in the city of Jakarta, received a heavier burden than men. These burdens perceived internally and externally. Internal burden is the burden that is felt in the lives of female domestic shutter and external load is felt in the public shutter poor women. This burden is also due to women living in poverty will try to keep life in many ways. Poor women must work to maintain family life and himself, though the choice is very limited work. Poor women are important actors in sustainable urban development through make community sustain. As a result of job choices, poor women are behind the effect and become input (input) for the balance of the ecosystem of Jakarta. If the input quality of the ecosystem conditions will lead to a balanced process that ultimately sustainable. This sustainability, will be transmitted to the sustainability of ecosystems nationally, regionally and globally.